The coevolution of lifespan and reversible plasticity - Irja I. Ratikainen (Nature Portfolio, 2019)
Reversible phenotypic plasticity is expected to be favoured by long lifespan, as this increases the environmental variation individuals experience. Here, the authors develop a model showing how phenotypic plasticity can drive selection on lifespan, leading to coevolution of these traits.